2022
DOI: 10.3390/antiox11030479
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Tripolyphosphate Nanoparticles Prepared by Ionic Gelation Improve the Antioxidant Activities of Astaxanthin in the In Vitro and In Vivo Model

Abstract: The present study aimed to investigate the effects of chitosan (CS)-tripolyphosphate (TPP) nanoparticles (NPs) on the stability, antioxidant activity, and bioavailability of astaxanthin (ASX). ASX-loaded CS-TPP NPs (ACT-NPs) prepared by ionic gelation between CS (0.571 mg/mL) and TPP (0.571 mg/mL) showed 505.2 ± 184.8 nm, 20.4 ± 1.2 mV, 0.348 ± 0.044, and 63.9 ± 3.0% of particle size, zeta potential, polydispersity index and encapsulation efficiency, respectively. An in vitro release study confirmed that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Since the 1990s, ionotropic gelation has been implemented in the development of polymeric biomaterials [ 50 ]. Chitosan structures encapsulating antibiotics [ 51 ], antioxidants [ 52 ] and growth mediators [ 53 ] have been acquired, exemplifying how adaptable this method is. This technique has so many advantages: it is simple, economical, and needs no complicated equipment or solvents, and takes a very short time to be completed [ 54 ].…”
Section: Methods Of Fabrication Of Chitosan Productsmentioning
confidence: 99%
“…Since the 1990s, ionotropic gelation has been implemented in the development of polymeric biomaterials [ 50 ]. Chitosan structures encapsulating antibiotics [ 51 ], antioxidants [ 52 ] and growth mediators [ 53 ] have been acquired, exemplifying how adaptable this method is. This technique has so many advantages: it is simple, economical, and needs no complicated equipment or solvents, and takes a very short time to be completed [ 54 ].…”
Section: Methods Of Fabrication Of Chitosan Productsmentioning
confidence: 99%
“…Higher entrapment efficiency (99.6%) was found with the indirect method. Entrapment efficiency is bound to increase with increasing concentration of TPP, because it acts as a polyanionic cross linker agent [34]. Use of PPC results in enormous attachment of drug molecules with those of the polymer with the aid of TPP, resulting in the entrapment of drug molecules [35].…”
Section: Percentage Yield and Entrapment Efficiencymentioning
confidence: 99%
“…Chitosan is the only positively charged polysaccharide and has been employed in various applications such as preparation of colloidal nanoparticles that wields interaction with negatively charged polyelectrolytes electrostatically [ 71 ]. Chitosan-based nanoparticles can be produced using various methods such as cross-linking process, ionic gelation and solvent evaporation [ 71 , 72 , 73 ]. This biopolymer-based formulation has been gaining interest by researchers due to numerous advantages.…”
Section: Nanocarrier Systems For Oral Delivery Of Astaxanthinmentioning
confidence: 99%
“…On the other hand, the FRAP values for free astaxanthin were reduced over time, which could be due to low solubility of free astaxanthin in the alkaline condition and decreased antioxidant activity of astaxanthin. It was suggested that these drawbacks can be overcome by encapsulating astaxanthin within the chitosan-based nanoparticles to enhance the bioavailability as well as providing a sustained release of oral astaxanthin [ 72 ].…”
Section: Nanocarrier Systems For Oral Delivery Of Astaxanthinmentioning
confidence: 99%
See 1 more Smart Citation